2018
DOI: 10.1101/352351
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ancestry of the two subgenomes of maize

Abstract: Maize (Zea mays ssp. mays) is not only one of the world's most important crops, but it also is a powerful tool for studies of genetics, genomics, and cytology. The genome of maize shows the unmistakable signature of an ancient hybridization event followed by whole genome duplication (allopolyploidy), but the parents of this event have been a mystery for over a century, since studies of maize cytogenetics began. Here we show that the whole genome duplication event preceded the divergence of the entire genus Zea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…The common ancestor of Zea and Tripsacum is predicted to have been adapted to tropical latitudes (Doebley, ; Edwards and Smith, ; McKain et al ., ). Therefore, the study of how natural selection adapted T. dactyloides to temperate climates represents an informative parallel to the adaptation of maize to temperate climates through artificial selection.…”
Section: Introductionmentioning
confidence: 97%
“…The common ancestor of Zea and Tripsacum is predicted to have been adapted to tropical latitudes (Doebley, ; Edwards and Smith, ; McKain et al ., ). Therefore, the study of how natural selection adapted T. dactyloides to temperate climates represents an informative parallel to the adaptation of maize to temperate climates through artificial selection.…”
Section: Introductionmentioning
confidence: 97%
“…A recent study suggests a common evolutionary relationship between maize and current day Urelytrum/Vossia which may provide clues to the nature of the parents of the allopolyploidy event that followed the speciation of ancestral maize and ancestral sorghum [26]. It has been suggested that these parents could be linked to the modern subgenomes in maize such that the origins of the subgenomes could be revealed, however for the purposes of this study we continue to use the definitions of Maize1 and Maize2 referred to in Schnable et al [15].…”
Section: Subgenome Assignments In Refgen_v4mentioning
confidence: 99%
“…Longer than a title, shorter than an abstract, and often including an important figure, you can get the gist of a lot of publications in short order. As an example, I can't honestly say that I would find or read the taxonomic literature these days, but a taxonomic researcher tweeted about his pre‐print publication identifying an obscure African grass as the ancestral relative of teosinte (predecessor of maize, Zea ) before the genome duplication (McKain et al, 2018); I was able to have a conversation and learn that it has not been studied in the U.S., is perennial, etc.—none of which was in his publication, yet directly relevant to my interest developing perennial maize.…”
Section: Five Audiences To Reachmentioning
confidence: 99%